2012
DOI: 10.1128/mcb.05878-11
|View full text |Cite
|
Sign up to set email alerts
|

Desumoylation of the Endoplasmic Reticulum Membrane VAP Family Protein Scs2 by Ulp1 and SUMO Regulation of the Inositol Synthesis Pathway

Abstract: Posttranslational protein modification by the ubiquitin-like SUMO protein is critical to eukaryotic cell regulation, but much remains unknown regarding its operation and substrates. Here we report that specific mutations in the Saccharomyces cerevisiae Ulp1 SUMO protease, including its coiled-coil (CC) domain, lead to the accumulation of distinct sumoylated proteins in vivo. A prominent ϳ50-kDa sumoylated protein accumulates in a Ulp1 CC mutant. The protein was identified as Scs2, an endoplasmic reticulum (ER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
4
17
0
Order By: Relevance
“…However, ulp2D cells have severe and diverse growth defects, including temperature sensitivity, sporulation defects, hypersensitivity to DNA damage, and hypersensitivity to ER stress, implying multiple substrates linked to growth regulation and stress resistance Hochstrasser 1999, 2000;Strunnikov et al 2001;Kroetz et al 2009;Felberbaum et al 2012). Several recent studies, including the present work, have identified novel Ulp2 substrates (Cremona et al 2012;Srikumar et al 2013b), which will allow more precise analyses of the molecular basis for the defects associated with loss of Ulp2.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, ulp2D cells have severe and diverse growth defects, including temperature sensitivity, sporulation defects, hypersensitivity to DNA damage, and hypersensitivity to ER stress, implying multiple substrates linked to growth regulation and stress resistance Hochstrasser 1999, 2000;Strunnikov et al 2001;Kroetz et al 2009;Felberbaum et al 2012). Several recent studies, including the present work, have identified novel Ulp2 substrates (Cremona et al 2012;Srikumar et al 2013b), which will allow more precise analyses of the molecular basis for the defects associated with loss of Ulp2.…”
Section: Discussionmentioning
confidence: 58%
“…A difficulty in studying aspects of polySUMO function in yeast has been the lack of effective affinity reagents for isolating polySUMO-modified proteins. Available antibodies to yeast SUMO (Smt3) are not effective for immunopurification of conjugates, and epitope tagging Smt3, while useful, leads to a strong reduction in SUMO conjugation efficiency (Wohlschlegel et al 2004;Hannich et al 2005;Felberbaum et al 2012). We show in the present work that a 160-residue fragment of the Slx5 STUbL, which bears four tandem SIMs, has high affinity for polySUMO and yeast HMW-SUMO conjugates.…”
Section: Discussionmentioning
confidence: 70%
“…While many phenotypic defects of ulp2 mutants have been documented, including sensitivity to a variety of stresses, genomic instability, and misregulation of the rDNA locus, much remains unknown regarding the physiological functions of Ulp2 (Li and Hochstrasser 2000;Bylebyl et al 2003;Felberbaum et al 2012). Few protein targets for desumoylation by Ulp2 have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis can explain our observation that acute administration of 5-HT 1A -R agonist, 8-OH-DPAT, significantly increased sumoylated 5-HT 1A -Rs. Several proteins have been reported to be sumoylated in the ER (Felberbaum et al, 2012; Majumdar et al, 2011; Yip et al, 2012). For example, sumoylation of transcription factor X box-binding protein 1(XBP1) in the ER results in accumulation of the protein in the ER, reduction of its activity and increases in ER stress responses (Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%